Method of automation of chemical desalination of water at TashChP - Zohid Y. Hasanov; Xayrulla S. Isakhodjayev; Anvar I. Anarbaev (PROBLEMS OF ENERGY AND SOURCES SAVING, 2026)
Relevance: thermal power plants (TPP, TChP) are among the largest consumers of water. They are characterized by a large amount of wastewater and pollution, which are dangerous for the natural environment. The wastewater from the chemical plant of TashTChP is largely formed by water from loosening rinses, spent regeneration solutions and wash water from ion-exchange filters. For chemical desalination plants, part of the effluent contains excess acid, usually sulfuric acid, part of the effluent contains excess alkali, and the neutralized effluent contains a significant amount of salt components, often exceeding maximum permissible concentrations (MPC), for example, for sulfates and chlorides. Aim: to analyze and substantiate the application of the electrical conductivity measurement method, followed by the algorithmization of salt concentration calculation in water, to improve the control of regeneration processes for hydrogen-cation exchange demineralization filters at a thermal power plant. Methods: the electrical conductivity measurement method and algorithmization of salt concentration calculation in water are utilized. Results: Automation of water-chemical regime control processes and cation exchange resin regeneration processes in filters optimizes reagent and water consumption, and reduces downtime of filtration equipment.